Pemanfaatan Aromaterapi untuk Mengurangi Nyeri Persalinan 1Kala ( Fase Aktif Use of Aromaherapy to Reduce Labor Pain in the 1 scale Active Phase - Pricilia Yunika, Regina; Ulya, Yadul; Maya Herlina, Siskha (Journal of Fundus, 2023)
The pain of uterine contractions can cause an increase in the sympathetic nervoussystem, changes in blood pressure, heart rate, breathing and if not treated immediatelywill increase feelings of worry, tension, fear and stress. Pain reduction management isvery important so that the entire birth process is safe and comfortable for both themother and the fetus that will be born. Childbirth pain can be treated with aromatherapybecause it is believed to be a complementary therapy to reduce the intensity of pain,namely with essential oils derived from the fragrant smell of plants to reduce healthproblems, the smell has a calming effect on the brain during childbirth. This study aimsto determine the use of aromatherapy to reduce labor pain during the first active phase.The method used in this research is quantitative. Determining the sample uses a totalsampling technique, namely by taking all members of the population. The sample in thisstudy were postpartum mothers at the Siti Hajar Islamic Hospital, Mataram District,Mataram City, West Nusa Tengggara. The results of the research were that the majority of respondents did not use aromatherapy to reduce pain, namely 14 (93.3%) people and a small percentage used aromatherapy to reduce pain, namely 1 (6.7%) people.